EFFECTIVENESS OF DYSMENORRHEA THERAPY EXERCISE AND TURMERIC-TAMARIND HERBAL DRINK ON REDUCING DYSMENORRHEA LEVELS IN STIKES TULUNGAGUNG STUDENTS - Ria Anggraini; Andyanita Hanif Hermawati (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Dysmenorrhea is a stabbing pain in the lower abdomen and thighs, commonly affecting women aged 18–21 years, often due to immature reproductive organs. Many young women are unaware of effective pain reduction methods. This study aimed to examine the effectiveness of dysmenorrhea therapy exercise and turmeric-tamarind herbal drink in reducing menstrual pain among STIKES Tulungagung students. A quasi-experimental design with two intervention groups using a pretest–posttest approach, involving 30 female students aged 18–23 years with regular cycles and pain scores of 1–10 on the NRS. Interventions included dysmenorrhea exercise or turmeric-tamarind drink for three days. Pain levels were measured using the Numeric Rating Scale, and data were analyzed using the Wilcoxon test (p < 0.05). Both groups showed significant reductions in pain (p < 0.001). These results support the adoption of non-pharmacological methods such as exercise and herbal drinks for dysmenorrhea management in educational health promotion programs.